2017
DOI: 10.1002/jcc.25089
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Analysis of Conjugated Hydrocarbons Using the Interacting Quantum Atoms Method

Abstract: A number of aromatic, antiaromatic, and nonaromatic organic molecules was analyzed in terms of the contributions to the electronic energy defined in the quantum theory of atoms in molecules and the interacting quantum atoms method. Regularities were found in the exchange and electrostatic interatomic energies showing trends that are closely related to those of the delocalization indices defined in the theory. In particular, the CC interaction energies between bonded atoms allow to rationalize the energetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Two new local minima for structures 45 and 46 (two valence isomers) with C 2 symmetry and less strain compared to the original structures (symmetry C 2v ) were found, Scheme 1; also see SI for Cartesian coordinates. Structures 55,57,61,72,73,74,97,127 and 129 with a triple bond in a cyclopropane framework rearranged to other structures during optimization so neither of them is included in our analysis. Finally, two 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 structures (201 and 202) were eliminated from our final analysis due to considerable multireference character.…”
Section: Test Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Two new local minima for structures 45 and 46 (two valence isomers) with C 2 symmetry and less strain compared to the original structures (symmetry C 2v ) were found, Scheme 1; also see SI for Cartesian coordinates. Structures 55,57,61,72,73,74,97,127 and 129 with a triple bond in a cyclopropane framework rearranged to other structures during optimization so neither of them is included in our analysis. Finally, two 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 structures (201 and 202) were eliminated from our final analysis due to considerable multireference character.…”
Section: Test Setmentioning
confidence: 99%
“…[54][55][56][57][58][59][60] Structural, energetic and electronic indices (SEE) are all defined on the basis of ground-state characteristics of a molecule. Recently, a theoretical link between SEE criteria is elaborated [50,61] within the framework of quantum chemical topology. [62,63] On the other hand, magnetic properties are response properties; this means a molecule, say benzene, does not sustain ring current in the absence of an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Latin America have also used topological analyses of the electron density to study noncovalent interactions in excited states as well. Jara-Cortés et al [61] employed QTAIM and NCI approaches to examine the reasons underlying the further stabilization of the D 6h benzene and D 2h naphthalene dimers in the first singlet excited state as compared to S 0 , that lead to the formation of the corresponding excimers. These authors found that the intermolecular ED is considerably larger in S 1 compared to S 0 .…”
Section: Electronic Excited Statesmentioning
confidence: 99%
“…The delocalization indicators that generate these methods can be classified in four main groups. Indicators that come from a manipulation of the wave function, the natural bond orbital (NBO) analysis is one of the most used; indicators constructed from the electron density and related quantities, the atoms in molecules theory has been extensively used; indicators derived from the pair density, the electron localization function and the delocalization index are two of the most important methods; and indicators extracted from magnetic response properties, probably the most known of them is the nuclear independent chemical shifts (NICS) . This latter group is peculiar, it is the only one that depends on the properties of a perturbed system.…”
Section: Introductionmentioning
confidence: 99%